New Straits Times, 14 December 2008 (The New Straits Times Press (M) Bhd, 2008)
More than 50 Orang Asli from Kampung Dusun. Chini here today staged a protest alleging that forest-based livelihood was affected after about 16ha of their village land was trespassed upon by outsiders.